Pengaruh Temperatur Post Weld Heat Treatment (PWHT) Terhadap Sifat Mekanis Material Baja A36 Yang Mengalami Pengelasan Shielded Metal Arc Welding (SMAW) - Akhyar, Waldi Naziful; Afrizal, Efi; Fatra, Warman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Some industries involve the welding process at the production stage. Currently in the practice widely used is SMAW (Shielded Metal Arc Welding) due to requires electrical energy as the heat source. In another line, that process produced residual stress since speed of cooling time is diffference between based metal and welded region. In this study, PWHT (Post Weld Heat Treatment) proposes to apply as solution in reduce the effect of residual stress. The method is the welded material reheated on temperature 450oC, 550 oC , and 650 during 1 hour in the furnace and cooled in it. The results showed at the highest heating temperature, elongation of welded material increase 22%, the hardness in the welding region decreased to 160 VHN while in the HAZ area the hardness was an improvement to 140 VHN, and the micro observations showed a structure after PWHT more uniform. It could be concluded that PWHT has succeeded in increasing the ductility of the welded materials. Key words : welded, PWHT, SMAW